Successful Treatment of Bleeding Gastric Varices with Splenectomy in a Patient with Splenic, Portal, and Mesenteric Thromboses - Lior Menasherian-Yaccobe; Nathan T. Jaqua; Patrick Kenny (Case Reports in Surgery)
A 59-year-old female with a history of multiple splanchnic and portal thromboses treated with warfarin underwent an esophagogastroduodenoscopy for cancer screening, and a polypoid mass was biopsied. One week later, she was admitted with upper gastrointestinal hemorrhage. Her therapeutic coagulopathy was reversed with fresh frozen plasma, and she was transfused with packed red blood cells. An esophagogastroduodenoscopy demonstrated an erosion of a gastric varix without evidence of recent bleeding. Conservative measures failed, and she continued to bleed during her stay. She was not considered a candidate for a shunt procedure; therefore, a splenectomy was performed. Postoperative esophagogastroduodenoscopy demonstrated near complete resolution of gastric varices. One year after discharge on warfarin, there has been no recurrence of hemorrhage. Gastric varices often arise from either portal hypertension or splenic vein thrombosis. Treatment of gastric variceal hemorrhage can be challenging. Transjugular intrahepatic portosystemic shunt is often effective for emergency control in varices secondary to portal hypertension. Splenectomy is the treatment for varices that arise from splenic vein thrombosis. However, treatment of gastric variceal hemorrhage in the context of multiple splanchnic and portal vein thromboses is more complicated. We report splenectomy as a successful treatment of gastric varices in a patient with multiple extrahepatic thromboses.